Development and implementation of a workshop for young adults with diabetes entering college and the workforce - West, Margaret; Sidhaye, Aniket; Thivierge, Meredith; Wolf, Risa M. (Frontiers in Endocrinology, 2023)
The process of transitioning from pediatric to adult diabetes care for adolescents and young adults is challenging. This transition period may include many life changes, and can be fraught with worsening glycemic control leading to increased risk for diabetes-related hospitalizations and complications. Research has demonstrated that increased support during this period can help maintain engagement in diabetes care. Transition guidelines highlight the importance of preparation and readiness for transition. In this article, we discuss the development, implementation and content of a workshop for patients and parents/caregivers preparing for the transition to college, the workforce and adult diabetes care.